Modern Energy Market Manipulation. - Kleit, Andrew N. (Emerald Publishing Limited, 2018)
This book explores the important economic and legal questionsof market manipulation that have arisen in restructured energy markets, paying particular attention to the actions of the Federal Energy Regulatory Commission.